2009
DOI: 10.1002/ppap.200800093
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Plasma‐Polymerized Top Layers on Composite Membranes: Influence on Separation Efficiency

Abstract: Plasma‐polymerized reverse osmosis membranes were prepared by deposition of an allylamine plasma‐polymerized top layer onto a cellulose ester surface. Their separation performance was highly dependent on the formation of the top layer, which was itself determined by the plasma polymerization conditions. The density and the thickness of the plasma‐deposited polymer top layer influence the membrane flux, while the ability of the membrane to reject salt relies on the degree of polymer cross‐linking, which is in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…When acrylic acid was mixed with He in order to achieve deposition in the microchannel, peaks of NH at 337 nm, CN at 359 nm and CO at 457 nm were observed in the emission spectrum. Similar peaks of NH and CN have been reported by Tran et al [43] during plasma deposition at atmospheric pressure. In this case it was observed that the intensities of the emission spectral lines decreased, which is most likely due to the presence of He metastables involved in breaking the chemical bonds of acrylic acid during additional reactions.…”
Section: Plasma and Film Characterization In Microchipsupporting
confidence: 74%
See 1 more Smart Citation
“…When acrylic acid was mixed with He in order to achieve deposition in the microchannel, peaks of NH at 337 nm, CN at 359 nm and CO at 457 nm were observed in the emission spectrum. Similar peaks of NH and CN have been reported by Tran et al [43] during plasma deposition at atmospheric pressure. In this case it was observed that the intensities of the emission spectral lines decreased, which is most likely due to the presence of He metastables involved in breaking the chemical bonds of acrylic acid during additional reactions.…”
Section: Plasma and Film Characterization In Microchipsupporting
confidence: 74%
“…Figure 3b shows the plasma emission spectrum of pure helium along with helium mixed with acrylic acid gaseous monomer. The peaks of the plasma emission spectra of He were identified as OH at 309 nm, N 2 at 315, 337 and 357 nm, N2 at 391 nm, He at 380, 587, 668 and 706 nm and, O at 780 nm [42][43][44]. Peaks corresponding to hydroxyl radical, nitrogen and oxygen indicate that the discharge channel is contaminated with air.…”
Section: Plasma and Film Characterization In Microchipmentioning
confidence: 99%
“…Composite membranes prepared by PECVD of allylamine464, 465 and acrylic acid463 onto porous UF membranes have demonstrated salt retention, comparable to RO and NF membranes. Additionally, the ultrathin coatings from PECVD of allylamine impart hydrophilicity to the top surface of a composite pervaporation membrane 465. Similarly, PECVD poly(thiophene) was grown on a porous membrane support and demonstrated for use in pervaporation 488…”
Section: Example Applicationsmentioning
confidence: 96%
“…In the case of an asymmetric membrane with very fine surface pores (e.g. for UF membranes), only the top surface of the membrane is functionalized if the side with the smaller pores is oriented towards the plasma 463–466. For membranes with larger pores, such as MF membranes, plasma can often permeate through the membrane.…”
Section: Example Applicationsmentioning
confidence: 99%
“…The helium–ethylenediamine discharge was generated at a power of 8 W, using a monomer flow rate of 10 sccm. The emission peaks were identified and assigned with reference to previous studies and to the online data available from the National Institute of Standards and Technology (NIST) . The emission spectrum of the pure helium discharge shows the presence of OH (309 nm), N 2 band (310–440), He (501, 587, 668, and 706 nm), and O (780 nm) lines.…”
Section: Resultsmentioning
confidence: 99%